Is GC bias in the nuclear genome of the carnivorous plant Utricularia driven by ROS-based mutation and biased gene conversion? - Ibarra-Laclette, Enrique (Landes Bioscience, 2011)
At less than 90 Mbp, the tiny nuclear genome of the carnivorous bladderwort plant Utricularia is an attractive model system for studying molecular evolutionary processes leading to genome miniaturization. Recently, we reported that expression of genes encoding DNA repair and reactive oxygen species (ROS) detoxification enzymes is highest in Utricularia traps, and we argued that ROS mutagenic action correlates with the high nucleotide substitution rates observed in the Utricularia plastid, mitochondrial, and nuclear genomes. Here, we extend our analysis of 100 nuclear genes from Utricularia and related asterid eudicots to examine nucleotide substitution biases and their potential correlation with ROS-induced DNA lesions. We discovered an unusual bias toward GC nucleotides, most prominently in transition substitutions at the third position of codons, which are presumably silent with respect to adaptation. Given the general tendency of biased gene conversion to drive GC bias, and of ROS to induce double strand breaks requiring recombinational repair, we propose that some of the unusual features of the bladderwort and its genome may be more reflective of these nonadaptive processes than of natural selection.